Financial Analysis of Establishing Cicendo Eye Center in Garut - Enang Suherman; Eka Purwanda (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
Engaging in business inevitably involves encountering many barriers and limits, such as the Shisendo Eye Clinic. While the primary focus of this project is eye health, it is crucial to do a comprehensive business feasibility analysis to prevent failures and mitigate any hazards in the future. This study aims to elucidate the business viability assessment for establishing the Cicendo Eye Clinic in the city of Garut, focusing on internal areas of the organization, including marketing, technical operations, management, and human resources. In this instance, the emphasis is primarily on the financial aspect. The employed techniques are both descriptive and analytical. Data collection methods encompass observation, interviews, document analysis, and literature review. Data analysis methods employ both qualitative and quantitative approaches. Qualitative data is essential for non-financial sectors, while quantitative data is necessary for financial and commercial sectors. The use of statistical techniques and the Microsoft Excel software program facilitates the analysis of quantitative data. According to the statistics and analysis of the establishment of the Garut Main Clinic of Centro Oftalmológico Sisendo, the clinic was able to recoup all investment expenses within three years of operation. The internal rate of return (IRR) is the discount rate at which the net present value of an investment becomes zero. A potential investment is considered viable if the internal rate of return (IRR) surpasses the anticipated rate. The internal rate of return (IRR) for the new clinic project at the 5-year Break Event Point (BEP) is 21.5% annually. Hence, this project is feasible and can be further pursued.